The Cambridge handbook of the dictionary - Finegan, Edward 1940-; Adams, Michael 1961- (Cambridge University Press, 2024)
There is no such thing as 'the dictionary'. Rather, there are innumerable kinds of dictionaries that respond to their authors' aspirations and their users' needs. In each case, the negotiation among a dictionary's material, its authors, and its readers tells a rich cultural story. Bringing together cutting-edge research from an international team of experts, this interdisciplinary Handbook provides an all-encompassing account of dictionaries in context. Organized into five thematic parts, its chapters cover a multitude of topics such as types of dictionaries, the place of dictionaries in intellectual, cultural and book history, and dictionaries as material objects, as well as their visual design. It also explores the role of dictionaries in a select group of special fields where words especially matter (for instance, law), the business contexts in which dictionaries are made, and finally the future of dictionaries. There is no fuller or more compelling overview of dictionaries available t
Title from publisher's bibliographic system (viewed on 23 Oct 2